Practical fitness profiling using field test data for female elite-level collegiate soccer players: A case analysis of a Division I team - Lockie, R. G.; Risso, F. G.; Giuliano, D. V.; Orjalo, A. J.; Jalilvand, F. (Strength and Conditioning Journal, 2018)
This article will provide practical examples of how field testing data can be presented to highlight the characteristics of individual soccer players. An example testing battery will be described, as will the process for converting test data into standardized scores. Data will be presented to show the strengths and weaknesses of certain players, and how this information can be used to inform individualized training programs. Examples of data comparisons to normative values for elite players will also be presented, in conjunction with discussion as to how this information can contribute to the practices of the strength and conditioning coach.